1970
DOI: 10.1172/jci106249
|View full text |Cite
|
Sign up to set email alerts
|

The effects of deoxygenation of adult and fetal hemoglobin on the synthesis of red cell 2,3-diphosphoglycerate and its in vivo consequences

Abstract: A B S T R A C T Patients over 1 month of age with arterial oxygen pressures of less than 60 mm Hg were found to have elevated red cell 2,3-diphosphoglycerate (2,3-DPG) levels and blood with a decreased affinity for oxygen. The increase in 2,3-DPG was proportional to the degree of hypoxemia. In patients under 1 month of age this relationship was not observed. Red cells from adults, but not newborns, showed rapid increases in 2,3-DPG when incubated under nitrogen. Adult, but not fetal, deoxyhemoglobin was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
2

Year Published

1971
1971
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(18 citation statements)
references
References 26 publications
1
14
1
2
Order By: Relevance
“…Maximal stimulation of red cell glucose consumption at pH 8.2 resulted in a greater increase in red cell 2,3-DPG in adults and subjects with a young red cell population than in neonates, suggestive of decreased flow through the 2,3-DPG bypass. It has also been reported (20) that red cells from adults, but not neonates, demonstrated a rapid increase in 2,3-DPG when incubated under nitrogen, although red cell glycolysis was stimulated in both adults and newborns.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Maximal stimulation of red cell glucose consumption at pH 8.2 resulted in a greater increase in red cell 2,3-DPG in adults and subjects with a young red cell population than in neonates, suggestive of decreased flow through the 2,3-DPG bypass. It has also been reported (20) that red cells from adults, but not neonates, demonstrated a rapid increase in 2,3-DPG when incubated under nitrogen, although red cell glycolysis was stimulated in both adults and newborns.…”
Section: Discussionmentioning
confidence: 73%
“…The concentration of G-6-P was elevated out of proportion to the age of the red cell population on the 1st day of life, continued to increase and peaked at 3-4 wk of age, at a time when the concentrations of red cell TTP and 2,3-DPG and the activity of PFK were similar to those observed at birth. Furthermore, the concentration of G-6-P correlated significantly with the plasma Pi concentration (20). These data suggested that the relative block in glycolysis at the PFK step and resulting pattern of glycolytic intermediates in term infants was not secondary to decreased PFK activity alone and that altered kinetic properties and/or modulation of PFK activity by extracellular factors such as Pi may also play a significant role at the in vivo level.…”
mentioning
confidence: 73%
“…Both 2,3-DPG and ATP had little effect on altering the oxygen affinity of fetal hemoglobin while their effect on the oxygen affinity of adult hemoglobin was profound [6,15,30,37].…”
Section: Introductionmentioning
confidence: 91%
“…Thus, different P50 levels were achieved at consistent levels of anemia (8 g/100 ml of blood) by a variety of maneuvers including rapid bleeding, slow bleeding, and recovery from severe anemia. Values for Pso were determined as described by Oski, Gottlieb, Miller, and Delivoria-Papadoupolous (14).…”
Section: Groups Of Studiesmentioning
confidence: 99%
“…However, many facets of this reflex are still obscure. It is not yet clear whether the peripheral arterial chemoreceptors sense oxygen tension or content Received for publication 14 February 1974 and in revised form 23 September 1974. of arterial blood (1). There is also considerable uncertainty concerning the effects of anemia upon ventilation per se and upon the ventilatory response to hypoxia (2,3).…”
Section: Introductionmentioning
confidence: 99%